Morphology of the Stomach of Tayra (Eira barbara) - Lima, André Luis de Sousa Nogueira; Gonçalves, Thamara Cozzi; Branco, Érika Renata; Rodrigues, Rogério Antônio Ribeiro; Giese, Elane Guerreiro; Carmo, Daiane Costa do; Santos, Juliana Teixeira; Lima, Ana Rita de (Acta Scientiae Veterinariae, 2018)
Background: The Tayra (Eira barbara) is a mammal of the family Mustelidae with a significant presence in Latin America, it is considered an opportunist and extremely agile omnivorous. Some organs compose the digestive system and the stomach is a substantial organ for this system. The stomach have a small and a large curvature and the regions of the cardia, fundus, body and pylorus. Histologically, the stomach is made up of four layers or tunics that contributes in digestive functions. However, due the limited information available in the literature about morphophysiology of wildlife, this study aimed to clarify the morphology of Eira barbara stomach to understand your digestive system. Materials, Methods & Results: Three males and three females of Eira barbara species were studied (all young adults), all samples were originated of the Bauxite Mine area, in Paragominas, Pará state, Brazil provided of donation to Morphological Animal Research Laboratory (LaPMa) of the Universidade Federal Rural da Amazonia (UFRA), after death by trampling. The corpses were treated with aqueous 10% formaldehyde solution intramuscular injections, subcutaneous and intracavitary. After dissection, the collected material was processed following histologic standard protocols for the subsequent preparation of slides. The studied animals showed the stomach on the left antimere the abdominal cavity, with saccular format with the presence of large and small curvatures. The organ showed composite mucosa made with various gastric folds distributed in regions of the cardia, fundus and pylorus. A microscopic analysis of Eira barbara stomach revealed the presence of tunics or layers which gradually invaginate the lumen of the organ and underlying lamina propria was located to the prismatic epithelium and muscular mucosae and mucosa itself. In the region of the cardia, the muscle layer was deeply situated on the lamina propria, consisting of smooth muscle tissue with circular and longitudinal fibers. The submucosa consists of loose connective tissue; it is much thicker than the lamina propria and has many vessels. The first portion of the stomach showed long glands, while with short pits. In light microscopy, the fundic region revealed the presence of a highly pleated epithelium with elongated glands composed of clear and basally placed cells, with flattened nuclei. These cells are named mucous. Along the short region of the gastric pits, the presence of large cells was reported, pyramidal or rounded, central nucleus, called parietal. The pyloric region microscopy revealed the presence of short glands, similar to those previously described in the cardia region. The wide presence of goblet cells in the final portion of the pylorus indicated gradual transition between the regions of the stomach to the intestine, called duodenum-pylorus transition. The muscular layer showed thick muscle bundles just in circular direction, being responsible for the formation of the pyloric sphincter. Discussion: The morphological analysis of the stomachs showed morphological and topographical similarities to the literature description for pets and wild mammals, however, were found in abundant quantities goblet cells in the transition duodenal pylorus. The goblet cells are located throughout the length of the small and large intestine and are responsible for the production and maintenance of the protective mucus synthesizing as glycoproteins known as mucins.